The Roles of Nigeria in Democratising Member States of ECOWAS - Alhaji, Abubakar Umar; Mohammed, Asmau; Doho , Ahmed Wali; Tal, Mohammed Kwarah (Kashere Journal of Politics and International Relations, 2025)
Nigeria pivotal role in the democratisation of West Africa through the Economic Community of West African States (ECOWAS) illuminates its enduring commitment to regional stability and democratic governance. Against this backdrop, Nigeria is determined to ensure democratic rules over military dictatorship in all countries of West Africa. The article aimed at explaining the role of Nigeria in democratising member states of ECOWAS sub-region. The article employs qualitative research design in data collection with a comprehensive content analysis approach. The results show that Nigeria has actively engaged in diplomatic mediation and conflict resolution while also leveraging coercive measures and peacekeeping efforts to support countries like Niger, Mali, Burkina Faso, and Gambia in their democratic journeys. Furthermore, Nigeria's provision of technical assistance underscores its leadership as a stabilising force within ECOWAS. Collectively, these initiatives not only reflect Nigeria’s strategic foreign policy objectives but also highlight its responsibility as a key regional actor dedicated to fostering democracy and peace across West Africa.